النثر الأندلسي في وصف الطبيعة في عصري ملوك الطوائف والمرابطين /‏ - Hishomudin Ahmad (Kulliyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2010)
This study discusses al-Andalusian prose on nature in the periods of Muluk al-Tawacif and al-Murabitin in order to fill a gap in literature studies that focus solely on the poetical part of nature. The Arab Andalusian literature (verses and prose) had achieved an outstanding achievement in these two periods. Therefore, the researcher tries to examine the prose texts on nature that were produced by the writers of those periods, study the genres of prose on nature, highlight the backgrounds of the writers, clarify literary styles and, expose the creativity and ingenuity in these texts. This study relies on two main methods, inductive and analytical. It is concluded from this study that the Andalusian prose was at its climax in the hands of great writers in those two periods. Nature was mostly described in all genres of prose; the most famous are the letters. These literary genres have good quality in the structure of the prose, expression and composition, imagination and literary images, and rhythm .All these elements made those prose distinguished literature. In addition, the emergence of new topics also shows the outstanding talent of the Andalusian writers in describing nature in their prose texts.